Schiff base derived from thiosemicarbazone and anthracene showed high potential in overcoming multidrug resistance in vitro with low drug resistance index - Bai J; Wang RH; Qiao Y; Wang A; Fang CJ (Dove Medical Press, 2017)
Jie Bai,1 Rui-Hui Wang,1 Yan Qiao,2 Aidong Wang,3 Chen-Jie Fang1 1Department of Chemical Biology, School of Pharmaceutical Sciences, Capital Medical University, Beijing, 2Department of Pathophysiology, School of Basic Medical Sciences, Zhengzhou University, Zhengzhou, Henan, 3Department of Pharmaceutical Engineering, College of Chemistry and Chemical Engineering, Huangshan University, Huangshan, Anhui, China Abstract: Multidrug resistance (MDR) is a huge obstacle in cancer chemotherapeutics. Overcoming MDR is a great challenge for anticancer drug discovery. Here, DNA binding and cytotoxicity of Schiff base L1 and L2 were explored to assess their efficiency in fighting cancer and overcoming the MDR. L1 and L2 could treat extremely chemoresistant MCF-7/ADR cell as drug-sensitive cell, with drug resistance index (DRI) <2.13, showing high potential in overcoming the MDR. The apoptotic ratio induced by L1 and L2 was low for both MCF-7 and MCF-7/ADR cells. L1 and L2 induced an impairment of cell cycle progression of MCF-7 and MCF-7/ADR cell lines and suppressed cell growth by perturbing progress through the G0/G1 phase, with L2 causing more profound effect, which might account for lower drug resistance after L2 treatment. The molecular docking revealed weak interaction between L1/L2 and P-glycoprotein (P-gp), the most important drug efflux pump and intracellular Rhodamine 123 accumulation indicated that the activity of P-gp was not inhibited by L1 and L2. Combined with the cellular uptake results, it implied that L1 and L2 could bypass P-gp efflux to exert anticancer activity. Keywords: DNA intercalating, antiproliferation, multidrug resistance, P-glycoprotein